Exploring the multifaced influencing factors of corporate social responsibility in Chinese-listed manufacturing enterprises - Cao, Chengzhe; Wu, Renhong; Hossain, Md Alamgir; Zhang, Huaihai (Asian Economic and Financial Review, 2024)
Although scholars have conducted research on the corporate social responsibility (CSR) of Chinese firms from different perspectives, there has been no unified conclusion so far. Therefore, identifying the factors that influence CSR in Chinese enterprises is an important topic for further investigation. Does the debt leverage ratio, ownership type, degree of internationalization (DOI), and auditing by the Big Four accounting firms have an impact on CSR? Based on a series of questions, our study aims to explore the influencing factors and relationships of CSR from multiple angles. Using data from 252 Chinese A-share listed enterprises from 2014 to 2019 and the CSR scores from the Hexun.com rating index, we constructed a panel dataset comprising 1,414 firm-year observations. After comparing models, the fixed effects method of panel data is ultimately used for empirical regression. The research results indicate a significant negative correlation between the leverage ratio and CSR. State-owned enterprises (SOEs) outperform non-state-owned enterprises (non-SOEs) in terms of CSR. There is a significant positive correlation between DOI and CSR. However, the contribution of audits by the Big Four accounting firms to CSR in Chinese enterprises is limited. While our study examines many aspects of the elements that affect corporate social responsibility (CSR) in Chinese companies, each firm must consider its circumstances and apply suitable strategies to improve its CSR practices.